2014
DOI: 10.2478/s11535-014-0338-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of smoke water and karrikin on seed germination of 13 species growing in China

Abstract: Plant-derived smoke water (SW), derived from combusted plant material, has been shown to stimulate seed germination and improve seedling vigor of a number of plant species from fire-dependent Mediterranean-type climate areas. The effects of SW on seed germination of 13 plant species from southern tropical and subtropical monsoon climate regions of South China are reported for the first time in this study using laboratory and pot trials. Among the 13 species tested, only Aristolochia debilis showed a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 44 publications
1
14
0
2
Order By: Relevance
“…Zhou et al [19] reported that butenolide enhanced the expression of two GAs biosynthesis genes (GA3ox1 and GA3ox2) during seed imbibition. Furthermore, Meng et al [34] demonstrated that karrikins delayed soybean seed germination through enhancing ABA biosynthesis, while impairing GAs biogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al [19] reported that butenolide enhanced the expression of two GAs biosynthesis genes (GA3ox1 and GA3ox2) during seed imbibition. Furthermore, Meng et al [34] demonstrated that karrikins delayed soybean seed germination through enhancing ABA biosynthesis, while impairing GAs biogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite some differences in the number of germinated seeds in both experiments, the SGV treatment was effective in terms of stimulation or inhibition also when the seeds were covered by a soil layer (Figure 7). Although the variance within a seed lot acid, IAA), or gibberellins [33][34][35][36]. The growth responses of hypocotyls or radicles grown from SGV-treated seeds also suggest the involvement of gibberellins [35].…”
Section: Seed Germination and Seedling Development In The Soilmentioning
confidence: 99%
“…Although the variance within a seed lot acid, IAA), or gibberellins [33][34][35][36]. The growth responses of hypocotyls or radicles grown from SGV-treated seeds also suggest the involvement of gibberellins [35]. Keeping in mind all the information gathered, the inhibitory effect of SGV has to be explained, too.…”
Section: Seed Germination and Seedling Development In The Soilmentioning
confidence: 99%
“…These include the arable weeds Brassica tournefortii and Sisymbrium orientale (Brassicacaeae) (Stevens et al 2007), and Avena fatua and Sorghum halepense (Poaceae) (Daws et al 2007). A recent study of the effects of smokewater and KAR 1 on seed germination of 13 species from South China identified only one (Aristolochia debilis; Aristolochiaceae) as responding positively to 1 nM KAR 1 or more (Zhou et al 2014). However, classifying a species in a binary fashion as karrikinresponsive or karrikin-non-responsive is fraught with difficulties, because environmental factors (e.g.…”
Section: Seed Germination Responses To Karrikinsmentioning
confidence: 99%